BALANCE BETWEEN PUBLIC AND PRIVATE ASPECTS IN ECONOMIC LAW: AN ANALYSIS OF THE ROLE OF STATE REGULATION AND RELATIONS BETWEEN BUSINESS ACTORS IN INDONESIA - Gunawan Widjaja; Dyah Ersita Yustanti; Rio Johan Putra (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyse the balance between public and private aspects in economic law in Indonesia, with a focus on the role of state regulation and the dynamics of relationships between business actors. National economic law requires integration between the public interest represented by the state as regulator and the interests of individuals or business entities regulated through private contracts. Through a literature review approach, this study examines various laws and regulations, court decisions, and related scientific literature. The results of the study indicate that state regulation plays an important role in creating a healthy business climate, preventing monopolistic practices, and protecting the rights of consumers and small businesses. On the other hand, relationships between business actors are regulated within the framework of national economic law, which emphasises the principle of freedom of contract while still considering public interests. Synergy between state regulations, business actor compliance, and oversight by relevant institutions is key to creating a fair, inclusive, and sustainable business ecosystem in Indonesia.